The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00223-017-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Fluorosis Due to Fluorocarbon Inhalation from an Air Dust Cleaner

Abstract: Skeletal fluorosis (SF) is an osteosclerotic metabolic bone disorder caused by excessive ingestion or inhalation of fluoride. SF is extremely rare in developed countries. We report a case of SF due to inhalational abuse from a fluoride-containing air dust cleaner. A 33-year-old man with no past medical history presented with progressively worsening low back pain for 2 years. Physical examination was notable for loss of lumbar lordosis and tenderness over the lumbar spine. Radiographs were notable for uniform g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Osteosclerosis on imaging and bone biopsy are consistent with the disease. Secondary hyperparathyroidism is also frequently noted [3,4]. While elevated serum, urine, and bone fluoride levels are usually seen, urinary fluoride levels can remain elevated despite normal serum levels following cessation of inhalant abuse, as occurred in our case (the patient had refrained for two months prior to presentation due to psychiatric hospitalization) [5][6][7].…”
Section: Discussionmentioning
confidence: 49%
“…Osteosclerosis on imaging and bone biopsy are consistent with the disease. Secondary hyperparathyroidism is also frequently noted [3,4]. While elevated serum, urine, and bone fluoride levels are usually seen, urinary fluoride levels can remain elevated despite normal serum levels following cessation of inhalant abuse, as occurred in our case (the patient had refrained for two months prior to presentation due to psychiatric hospitalization) [5][6][7].…”
Section: Discussionmentioning
confidence: 49%
“…In the process of the incomplete combustion of coal, oil, gas, and garbage, polycyclic aromatic hydrocarbons are produced, in the group of which there are such compounds as benzofluorants, fluorants, and fluorens. Benzofluorants have a strong carcinogenic effect through the formation of metabolites in the human body that initiate the development of the neoplastic process [ 112 ]. In areas where fluorine-containing fuel is used for smoking and where fluorine-containing fertilizers are produced and used in agriculture, the concentration of this element in the air is increased, which leads to increased exposure by inhalation.…”
Section: Sources Of Fluoridementioning
confidence: 99%
“…However, he denied high F exposure including from excess black tea, (6)(7)(8)(19)(20)(21)(22) ingestion of toothpaste, (16,21,23) or inhalation of a fluorocarbon. (17,(24)(25)(26)(27)(28) Then, his mother revealed that he had inhaled several times daily for 2-3 years, reportedly for pain control, computer 'duster' that we found contains difluoroethane (DFE). Subsequently, the patient confirmed this practice, using Dust-Off (Falcon Safety Products, Branchburg, JN, USA), but despite his skeletal disease indicating more prolonged exposure was adamant the duration was not longer.…”
Section: C) Sf Diagnosis and Treatmentmentioning
confidence: 99%
“…Huffing fluorocarbons can lead to euphoria, and abuse or dependence in 10-50% of cases. (25) The first, reported 42 years ago by Klemmer and Hadler, (27) involved an operating room nurse admitted to a clinical research unit for a puzzling bone disease who was discovered in possession of cotton wadding soaked in methoxyflurane (an anesthetic). Her serum and urine F levels were much higher than ever subsequently recorded, likely explained by specimen collection shortly after inhalation.…”
Section: B) Non-endemic Skeletal Fluorosismentioning
confidence: 99%